Middle-Aged Indians with Type 2 Diabetes Are at Higher Risk of Biological Ageing with Special Reference to Serum CDKN2A. (24th March 2020) - Banerjee, Joyita; Dhas, Yogita; Mishra, Neetu
Abstract : Sedentary lifestyle and high visceral adiposity have elevated the risk of type 2 diabetes (T2DM) among Indians at younger age. In this study, we aimed to investigate the association of oxidative stress and chronic inflammatory mediators with ageing with special reference to the biological ageing marker cyclin-dependent kinase inhibitor 2A (CDKN2A) among middle-aged (31-50 years) Indian healthy and T2DM subjects. Malondialdehyde (MDA), oxidized LDL (oxLDL), interleukin-6 (IL-6), interleukin 1 β (IL-1 β ), tumor necrosis factor α (TNF- α ), monocyte chemoattractant protein-1 (MCP-1), and CDKN2A were measured in T2DM patients (n = 80 ) and controls (n = 80 ) aged 31-50 years, further grouped into G1: 31-40 years and G2: 41-50 years. IL-6, TNF- α, MCP-1, and CDKN2A showed a significant association with ageing among both T2DM patients and controls. But the strength of the association of MCP-1 and CKDN2A with ageing was significantly stronger in T2DM patients than the controls. All the oxidative stress and proinflammatory mediators showed nonsignificant associations with CDKN2A in the controls. However, IL-6, TNF- α, and MCP-1 showed a strong association with CDKN2A in T2DM patients. An increased risk of high levels of CDKN2A was found in G1 T2DM patients (OR: 3.484 (95% CI: 1.246-9.747) p = 0.017 ) and G2 T2DM patients (OR: 5.000 (95% CI: 1.914-13.061), p = 0.001 ) with reference to the respective control groups. Our study reveals that the middle-aged Indians with T2DM are at higher risk of biological ageing. The development of T2DM is more common among middle-aged Indians. T2DM may exacerbate the ageing process and may subsequently predispose Indians to various age-related complications at a much early age.